Some applications of a Wright distribution series on subclasses of univalent functions - SHRIGAN, Mallikarjun G.; BHOURGUNDE, Sidharam D.; SHELAKE, Girish D. (Studia Universitatis Babeș-Bolyai Mathematica, 2024)
The purpose of the present paper is to find the sufficient conditions for the subclasses of analytic functions associated with Wright distribution series to be in subclasses of univalent functions and inclusion relations for such subclasses in the open unit disk D. Further, we consider the properties of integral operator related to Wright distribution series. Mathematics Subject Classification (2010): 30C45.